Effect on ammonium bromide in dielectric behavior based alginate solid biopolymer electrolytes - A. F., Fuzalin; Nur Muhitul Jalilah, Rasali; Ahmad Salihin, Samsudin (IOP Publishing, 2018)
This paper present the development of solid biopolymer electrolytes (SBEs) system which has been accomplished by incorporating various composition of ionic dopant namely ammonium bromide (NH4Br) with alginate solution casting method. The prepared sample of SBEs has been analyzed via electrical impedance spectroscopy (EIS) showed that the ionic conductivity at room temperature was increased from 4.67 x 10-7 S cm-1 for un-doped sample to optimum value at 4.41 x 10-5 S cm-1 for composition of 20 wt. % NH4Br. The SBEs system was found to obey the Arrhenius characteristics with R2~1where all sample is thermally activated when increasing temperature. The dielectric behavior of the alginate-NH4Br SBEs system were measured using complex permittivity (ε*) and complex electrical modulus (M*) and shown the non-debye behavior where no single relaxation was found for present SBEs system.